The Influence of Storytelling Method and Scaffolding Learning on the Speaking Skills of Fifth Grade Students at SD Negeri 53 Malalin - Asrah Amir; Nuraini K; Aswadi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine the effect of the storytelling method and scaffolding learning on elementary students' speaking skills. The research problems are formulated to describe: (1) the effect of the storytelling method on the speaking skills of fifth-grade students at SD Negeri 53 Malalin, (2) the effect of scaffolding learning on their speaking skills, and (3) the combined effect of the storytelling method and scaffolding learning on the speaking skills of the same students. This study was motivated by the low speaking ability among fifth-grade students at SD Negeri 53 Malalin. The research employed a quantitative approach with a quasi-experimental design, specifically a posttest-only control group design. The independent variables were the storytelling method (X₁) and scaffolding learning (X₂), while the dependent variable was speaking ability (Y). The sample consisted of 32 students, divided equally into experimental and control groups. Data were collected through posttests and documentation, and analyzed using descriptive and inferential statistics, including mean, standard deviation, and the independent samples t-test. The average posttest score in the experimental group was 81.5625, while the control group scored 68.4375, with standard deviations of 6.25000 and 4.36606, respectively. The calculated t-value (7.11) exceeded the t-table value (±2.042), indicating a significant effect of the storytelling method. For scaffolding learning, the experimental group scored an average of 85.9375, compared to 68.4375 in the control group, with standard deviations of 4.5527 and 4.36693. The t-value (11.09791) again exceeded the critical value, confirming a significant effect. Finally, the combined application of both methods yielded an experimental group average of 89.3750, with a t-value of 14.92213 and standard deviations of 3.67394 and 4.18027, indicating a significant influence on students’ speaking skills. These findings demonstrate that the use of storytelling and scaffolding methods significantly enhances the speaking abilities of fifth-grade students at SD Negeri 53 Malalin.